PENINGKATAN POTENSI BATU PADAS LADGESTONE SEBAGAI ADSORBEN ION LOGAM BERAT Cr(III) DALAM AIR MELALUI AKTIVASI ASAM DAN BASA - Diantariani, N. P. (Jurnal Kimia (Journal of Chemistry); Vol. 4, No. 1 Januari 2010)
The research with aim to increase potency of natural batu padas of Ladgestone type through activation used by acid (H2SO4) and basa (NaOH) various concentrations (2.0; 4.0; and 6.0N) to adsorption ability of heavy metal ion of Cr(III) in water have been done. Acid and base activated batu padas was characterizated of specific surface area with blue methylen method, whereas surface acidity determined by acid-base titration. Whereas, amount of Cr(III) which can of maximum adsorpted every weight of adsorben or adsorption capacity determined by atomic absorption spectrophotometer (AAS). The result measurement of activated batu padas compared by batu padas without activation (control). Result of research indicate that batu padas after activated by NaOH and of H2SO4 yield surface acidity (active sites) and realtive higher specific surface area compared with without activation (control). Maximum ability(capacity) adsorption to Cr(III) was just increasing for NaOH activated batu padas. Highest Capacities obtained by NaOH activated batu padas at concentration 4.0N was 2.0265 mg/g.
Keywords: batu padas Ladgestone, adsorbent, Cr(III), activation